Regulated Crystallization of Efficient and Stable Tin-Based Perovskite Solar Cells via a Self-Sealing Polymer - Liu, Gengling; Liu, Cong; Lin, Zhuojia; Yang, Jia; Huang, Zengqi; Tan, Licheng; Chen, Yiwang (ACS applied materials & interfaces, 2020)
Tin-based perovskite solar cells (PVSCs) have emerged as the most promising lead-free perovskite materials owing to their superior optoelectronic properties. However, the deficiency of accurate control of the tin-based perovskite crystallization process increases the possibility of unexpected perovskite film morphology and defects, resulting in inferior power conversion efficiency (PCE). Meanwhile, the poor environmental stability of tin-based perovskite films hinders its further development. In this work, a unique polymer [poly(ethylene-co-vinyl acetate) (EVA)] is introduced into anti-solvent during spin coating of formamidinium tin tri-iodide (FASnI3) precursor solution. The CO groups contained in EVA have a powerful Lewis acid–base complexation with uncoordinated tin atoms in perovskite grains, which can greatly improve the grain size, optimize the grain orientation, and decrease the surface defects of FASnI3 films. This strategy offers an impressive PCE of 7.72% with favorable reproducibility. More importantly, the PVSC devices based on FASnI3–EVA absorbers have a self-encapsulation effect, which exhibits distinguished moisture and oxygen barrier property, thereby retaining 62.4% of the original efficiency value after aging for 48 h in the air with a humidity of 60%. Such a convenient strategy provides a new inspiration for the establishment of stable and high-performance tin-based PVSCs.